ARABIC CLASS THEORY BY TAMMĀM HASSĀN AND IMPLICATIONS FOR ARABIC LANGUAGE TEACHING - Taufik Luthfi; Khaidir Maulana; Dina Karinda Dewi, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study analyzes Tammām Ḥassān’s conception of classifying Arabic word classes and its implications for Arabic language pedagogy in Indonesia. Building on the classical naḥw tradition that recognizes three categories (ism, fiʿl, ḥarf), the paper foregrounds Ḥassān’s sevenfold scheme ism, waṣf, fiʿl, ḍamīr, ẓarf, al-khalīfah, and al-ādāt grounded in the theory of taḍāfur al-qarāʾin and paired with his critique of the al-ʿawāmil framework. Using a qualitative-descriptive design and literature review of primary works al-Lughah al-ʿArabiyyah: Maʿnāhā wa Mabnāhā; Khulāṣah an-Naḥwiyyah, classical references al-Kitāb al-Inṣāf, and Indonesian grammar as comparator, the analysis maps the rationale behind the seven-way classification and evaluates its explanatory reach especially for items often forced into ism, such as ẓarf and ḍamīr. Findings indicate the scheme is more jāmiʿ–māniʿ, aligning formal marking, function, and contextual indicators via a network of qarāʾin, thus clarifying form–meaning relations. Pedagogically, integrating this taxonomy supports grammatical material design, functional mapping in clause analysis, and strategies attentive to contextual cues. The study recommends developing naḥw curricula in madrasahs/pesantren with Arabic–Indonesian contrastive modules, qarāʾin identification drills, and reading–writing assessments that evaluate category mapping, plus form–function rubrics and rigorous corpus-based evaluation of text comprehension.